HNBR Cathode Binder For Battery Cell Using Gamma-Verolactone As Processing Solvent

By developing a polymer composed of monomer units derived from 1,3-butadiene and acrylonitrile, which is dissolved in gamma-valerolactone and used as the binder for the cathode of the battery unit, the adhesive safety and environmental problems in the prior art are solved, and a cathode material with high electrochemical stability and low density is achieved.

CN119698697APending Publication Date: 2025-03-25ARLANXEO DEUT GMBH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202380062140.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-30
Filing Date
2023-08-28
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the prior art, adhesives used for the cathode of the battery unit such as polyvinylidene fluoride polymer (PVDF) have safety hazards and high density problems. At the same time, the traditional solvent N-methylpyrrolidone (NMP) is toxic and it is difficult to achieve green and safe battery production.

Method used

A polymer is developed that consists of monomer units derived from 1,3-butadiene and acrylonitrile and content is 65 wt.-% with a maximum proportion relative to the total weight, which is dissolved in a non-toxic and green solvent gamma-valerolactone for the manufacture of cathode binder for battery cells.

Benefits of technology

The polymer provides a cathode adhesive with high electrochemical stability and low density, which can be well mixed with gamma-valerol at room temperature to form a cathode slurry with high capacity and stability, solving the safety and environmental problems of traditional adhesives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a polymer comprising or consisting essentially of monomeric units derived from 1, 3-butadiene, acrylonitrile and optionally methacrylic acid, the weight content of monomeric units derived from 1, 3-butadiene being at most 65 wt.-% relative to the total weight of the polymer. The polymer can be used to make cathodes for battery cells. The invention further relates to a cathode of a battery cell comprising the polymer and to a composition comprising the polymer and gamma-valerolactone.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polymer comprising or essentially consisting of monomer units derived from 1,3-butadiene, acrylonitrile and optionally methacrylic acid, wherein the weight content of monomer units derived from 1,3-butadiene is at most 65 wt.-% relative to the total weight of the polymer. The polymer can be used to manufacture a cathode for a battery cell. The present invention further relates to a cathode for a battery cell comprising the polymer and to a composition comprising the polymer and gamma-valerolactone. Background Art

[0002] Rechargeable batteries (also called storage batteries, secondary batteries or accumulators) are a type of battery that can be charged, discharged and recharged multiple times. A battery cell includes electrodes (anode and cathode), an electrolyte and a separator. Within the electrodes, a polymer binder typically fixes the active material and the conductive material. The binder needs to be flexible and insoluble in the electrolyte. It should provide good adhesion to the current collector and have chemical and electrochemical stability. In addition, it should be applicable to the electrode in a simple manner.

[0003] N-Methylpyrrolidone (NMP) is often used as a solvent in cathode production. However, NMP is toxic and non-toxic alternatives are needed to allow safer and greener production of battery cells.

[0004] Polyvinylidene fluoride polymer (PVDF) is often used as a binder in cathode production. However, PVDF has several disadvantages because fluorine causes corrosion within rechargeable batteries and is inherently unsafe. Handling PVDF requires preventive safety measures because fluorine can form hydrogen fluoride. PVDF has a relatively high density and therefore increases the weight of the rechargeable battery.

[0005] As a non-toxic and green solvent, γ-valerolactone has been suggested to replace NMP. However, PVDF is almost insoluble in γ-valerolactone and requires extra effort and elevated temperatures to prepare cathode slurries and electrodes. Such solutions of PVDF in γ-valerolactone at high temperatures tend to form gels at room temperature after the solution cools.

[0006] VR Ravikumar et al., ACS Appl. Energy Mater. 2021, 4, 1, 696-703, relates to γ-valerolactone as an alternative solvent for the manufacture of lithium-ion battery electrodes.

[0007] JP 2017 045611 A relates to an all-solid secondary battery, which includes an anode active material layer, a solid electrolyte layer and a cathode active material layer in sequence. Among many other solvents, γ-valerolactone is mentioned as a solvent for the anode active material layer, which has a boiling point in the range of 180°C-300°C.

[0008] JP 2018 076417 A relates to a porous membrane which can be used as a separator and is produced using a porous membrane-forming composition containing a hydrophobically modified insulating fiber (A), a binder resin (B) and a solvent (S). Among many other solvents, γ-valerolactone is mentioned as the solvent (S).

[0009] WO 2015 073745 A2 relates to a battery comprising a first conductive substrate portion having a first face and a second conductive substrate portion having a second face opposite to the first face. Among many other solvents, gamma-valerolactone is mentioned as a solvent that can be used to prepare the cathode.

[0010] WO 0045452 A1 relates to a binder composition for electrodes of lithium ion secondary batteries. Among many other solvents, gamma-valerolactone is mentioned as an organic dispersion medium.

[0011] WO 2014 046521 A1 relates to a method for manufacturing a separator for a lithium secondary battery, a separator manufactured by the method, and a lithium secondary battery including the separator, the method comprising: a step of forming a porous coating layer containing inorganic particles on at least one side of a porous substrate; a charging step for forming charged polymer particles by charging the polymer particles; a transfer step for transferring the charged polymer particles to the upper surface of the porous coating layer to form a functional coating layer; and a fixing step for fixing the functional coating layer by heat and pressure. Among many other solvents, γ-valerolactone is mentioned as a non-aqueous electrolyte.

[0012] US 2020 0194837 A1 relates to an additive for lithium secondary batteries. Among many other solvents, γ-valerolactone is mentioned as an electrolyte.

[0013] EP 3 605 675 A1 discloses a polymer and its use as an adhesive. The polymer contains a conjugated diene monomer unit (e.g. 1,3-butadiene) and / or an alkylene structural unit and a monomer unit containing a nitrile group (e.g. acrylonitrile) and optionally other repeating units (e.g. (meth)acrylate monomers, such as n-butyl acrylate). The polymer is used as an adhesive together with PVDF.

[0014] There is a need for polymers that can be used as cathode binders and that have advantages over prior art polymers.

[0015] The object of the present invention is to provide a battery cell and a cathode thereof which have advantages over the prior art, especially in terms of safety and environmental issues. The polymer should overcome the disadvantages of PVDF and should be compatible with safer and greener solvents, especially γ-valerolactone, in order to overcome the disadvantages of NMP. Summary of the invention

[0016] This object has been achieved by the subject matter of the patent claims.

[0017] The present invention relates to a polymer comprising or essentially consisting of monomer units derived from 1,3-butadiene, acrylonitrile and optionally methacrylic acid, wherein the weight content of monomer units derived from 1,3-butadiene is at most 65 wt.-%, relative to the total weight of the polymer.

[0018] It has been unexpectedly found that such polymers have high electrochemical stability and can be easily dissolved in the non-toxic and green solvent γ-valerolactone at room temperature. Those binder solutions can be further processed at room temperature to obtain cathode slurries and cathodes that show very good electrochemical performance and stability. Preferably, these slurries are based on LFP.

[0019] Aspects of the invention relate to the use of a polymer as a binder in a cathode of a battery cell, to a cathode of a battery cell comprising the polymer, and to a composition comprising the polymer and gamma-valerolactone.

[0020] The polymers offer at least a suitable alternative to prior art cathode binders while overcoming the need to use polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP).

[0021] The polymer and cathode binder made from the polymer are free of PVDF, thus overcoming safety issues and corrosion problems during manufacture and use in battery applications.

[0022] The polymers exhibit at least equivalent or superior binder properties compared to conventional cathode binders based on PDVF.

[0023] The polymer has a lower density than PDVF and is advantageous in portable devices or electric vehicles using rechargeable batteries due to its reduced weight.

[0024] When used as a cathode binder, the polymer maintains capacity retention after charge, discharge, and recharge.

[0025] In the manufacture of cathodes for battery cells, the polymer can be advantageously processed with γ-valerolactone as a solvent, thereby avoiding the need for NMP. Binder solutions of the polymer in γ-valerolactone can be prepared at room temperature, allowing for smooth processing and preparation of electrodes. Electrochemical evaluation of the cathode showed high capacity and stability. DETAILED DESCRIPTION

[0026] In order to fully understand the present invention and its advantages, reference is made to the following detailed description. It should be understood that the various aspects and embodiments of the detailed description as disclosed herein are illustrations of specific ways to make and use the present invention and do not limit the scope of the invention when considering the claims and detailed description. It should also be understood that features from different aspects and embodiments of the present invention can be combined with features from different aspects and embodiments of the present invention.

[0027] The polymer according to the invention comprises or consists essentially of monomer units derived from 1,3-butadiene, acrylonitrile and optionally methacrylic acid, wherein the weight content of monomer units derived from 1,3-butadiene is at most 65 wt.-%, relative to the total weight of the polymer.

[0028] It has been surprisingly found that a maximum content of 1,3-butadiene (ie a minimum content of polar monomers including acrylonitrile and optionally methacrylic acid) provides good solubility in γ-valerolactone and performance as a binder in electrodes.

[0029] The term "monomer unit" means a structural unit derived from the monomer incorporated in the polymer backbone obtained by polymerizing the monomer. The skilled person recognizes that polymerization changes the monomer structure and such changes are indicated by the term "derived from". In addition, since the polymer according to the invention is preferably hydrogenated, this hydrogenation may further change the monomer units derived from the monomer. In particular, free radical polymerization of 1,3-butadiene using a suitable catalyst results in monomer units still having ethylenic unsaturation, which is fully or partially saturated during the subsequent hydrogenation process.

[0030] When fully hydrogenated, the residual double bonds are <1%, and when partially hydrogenated, the residual double bonds are <5%.

[0031] Preferably, the polymer is hydrogenated. Preferably, the content of residual C=C double bonds is at most 5%, more preferably at most 4%, relative to the content of C=C double bonds before hydrogenation. The hydrogenation is preferably carried out under conditions that do not substantially affect acrylonitrile and optionally methacrylic acid.

[0032] Preferably, the polymer has a weight content of monomer units derived from 1,3-butadiene in the range from 55 to 65 wt.-%, relative to the total weight of the polymer.

[0033] Preferably, the polymer has a weight content of monomer units derived from acrylonitrile of at least 25 wt.-%, relative to the total weight of the polymer. Preferably, the polymer has a weight content of monomer units derived from acrylonitrile in the range of 30 to 45 wt.-%, relative to the total weight of the polymer.

[0034] Preferably, the polymer has a weight content of monomer units derived from 1,3-butadiene ranging from 55 to 65 wt.-%; and a weight content of monomer units derived from acrylonitrile ranging from 35 to 45 wt.-%, relative to the total weight of the polymer.

[0035] In a preferred embodiment, the polymer does not comprise monomer units derived from methacrylic acid.Preferably, the polymer consists essentially of monomer units derived from 1,3-butadiene and acrylonitrile (copolymer, dipolymer).

[0036] In other preferred embodiments, the polymer additionally comprises monomer units derived from methacrylic acid.Preferably, the polymer consists essentially of monomer units derived from 1,3-butadiene, acrylonitrile and methacrylic acid (terpolymer).

[0037] Preferably, the polymer has a weight content of monomer units derived from methacrylic acid of at least 2.5 wt.-%, relative to the total weight of the polymer. Preferably, the polymer has a weight content of monomer units derived from methacrylic acid in the range of 2.5 to 7.5 wt.-%, relative to the total weight of the polymer.

[0038] Preferably, the polymer has, relative to the total weight of the polymer, a weight content of monomer units derived from 1,3-butadiene in the range of 55 to 65 wt.-%; a weight content of monomer units derived from acrylonitrile in the range of 30 to 45 wt.-%; and a weight content of monomer units derived from methacrylic acid in the range of 2.5 to 7.5 wt.-%.

[0039] Preferably, the polymer has a Mooney viscosity (ML 1+4 at 100°C) in the range of 45 to 100 MU, more preferably 55 to 90 MU, most preferably 60 to 70 MU.

[0040] In a preferred embodiment, the polymer consists essentially of monomer units derived from the following monomers in the following contents relative to the total weight of the polymer: 1,3-butadiene 62 ± 2 wt.-%, acrylonitrile 33 ± 2 wt.-% and methacrylic acid 5 ± 2 wt.-% (see Example C below).

[0041] In a preferred embodiment, the polymer consists essentially of monomer units derived from the following monomers in the following contents relative to the total weight of the polymer: 1,3-butadiene 61 ± 2 wt.-% and acrylonitrile 39 ± 2 wt.-% (see Example E below).

[0042] In a preferred embodiment, the polymer consists essentially of monomer units derived from the following monomers in the following contents relative to the total weight of the polymer: 1,3-butadiene 57±2 wt.-% and acrylonitrile 43±2 wt.-% (see Example F below).

[0043] The polymers according to the invention relate to different aspects of the invention.

[0044] A first aspect of the invention relates to the use of a polymer as a binder in the cathode of a battery cell.

[0045] A second aspect of the present invention relates to a cathode of a battery cell comprising the polymer.

[0046] A third aspect of the present invention relates to a composition for making a cathode of a battery cell, the composition comprising (i) a polymer and (ii) γ-valerolactone.

[0047] The method for making a polymer is not limited and the method can be according to methods known in the art. The method for making a polymer can be any one of solution polymerization, suspension polymerization, bulk polymerization and emulsion polymerization. The method for making a polymer can be free radical polymerization and living free radical polymerization.

[0048] The method for making the hydrogenated polymer is also not limited. The method for making the hydrogenated polymer can be any of oil layer hydrogenation or water layer hydrogenation. The homogeneous or heterogeneous hydrogenation catalyst for making the hydrogenated polymer can be any hydrogenation catalyst known in the art, such as palladium-based catalysts, ruthenium-based catalysts and rhodium-based catalysts or any combination thereof.

[0049] When the polymer is used as a cathode binder for a rechargeable battery, the binder fixes the active material and the conductive material within the cathode of the rechargeable battery. The polymer is then dissolved and / or dispersed in an organic solvent to form a binder solution, and gamma-valerolactone is preferably used as the solvent.

[0050] Before dissolving and / or dispersing, the polymer can be ground using a ball mill, sand mill, bead mill, pigment disperser, grinder, ultrasonic disperser, homogenizer, planetary mixer. Such devices can also be used to promote the dissolution and / or dispersion of the polymer in an organic solvent to form a binder solution.

[0051] The binder solution is then preferably mixed with the active material and the conductive material to form a cathode slurry composition.

[0052] The active material may be lithium nickel manganese cobalt oxide (abbreviated as Li-NMC, LNMC, NMC or NCM), which is a mixed metal oxide of lithium, nickel, manganese and cobalt. The active material may be lithium iron phosphate (LFP). The active material may be lithium manganese oxide (LMO). Lithium iron phosphate (LFP) is preferred.

[0053] The conductive material may be a carbon material such as carbon black (eg, acetylene black, furnace black), graphite (graphene), carbon fiber (carbon nanofiber, single-walled or multi-walled carbon nanotube (CNT), and vapor-grown carbon fiber), and carbon flakes.

[0054] The cathode slurry composition is then preferably applied to a current collector and then dried.

[0055] Application to the current collector may be performed by doctor blade coating, dip coating, reverse roll coating, direct roll coating, gravure coating, extrusion coating, rod coater and brush coating. The thickness of the cathode slurry composition on the current collector after application but before drying may be appropriately set.

[0056] The current collector is a material having electrical conductivity and electrochemical durability. The current collector may be made of iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold or platinum. The current collector may be in the form of a foil. The current collector is preferably aluminum foil due to its high electrical conductivity, electrochemical and chemical stability, and low cost.

[0057] Drying of the cathode slurry composition applied to at least one surface of the current collector is preferably achieved by warm, hot or low humidity air at ambient pressure; vacuum drying, infrared light irradiation drying or electron beam drying may also be used.

[0058] After drying, the cathode slurry composition applied to the current collector can be pressed by die pressing or roller pressing. Pressing provides a more uniform layer of dried material.

[0059] The resulting positive cathodes, including the polymer as a positive cathode binder, are then assembled to form a rechargeable battery.

[0060] The rechargeable battery is preferably assembled by stacking the positive cathode and the negative electrode with the separator therebetween, possibly rolling or folding the resulting stack according to the shape of the rechargeable battery to place the stack in a battery container, filling the battery container with an electrolytic solution, and then sealing the battery container.

[0061] In order to prevent the pressure increase within the rechargeable battery and the occurrence of overcharge or overdischarge, an overcurrent prevention device such as a PTC device or a fuse; an expanded metal such as sponge nickel; or a lead plate may be provided as needed.

[0062] The shape of the rechargeable battery may be, for example, a coin type, a coin type, a sheet type, a cylindrical type, a prismatic type, a pouch type, or a flat type.

[0063] The negative electrode can be any known negative electrode, for example, carbon materials such as amorphous carbon, natural graphite, artificial graphite, natural black lead, mesophase carbon microbeads, pitch-based carbon fibers, and silicon-graphite; conductive polymers such as polyacene or polyaniline; or metals such as silicon, tin, zinc, manganese, titanium oxide, iron, lithium (for half-cells) and nickel, including alloys of metals. The negative electrode is preferably graphite or silicon-graphite.

[0064] The separator may be a fine porous film or nonwoven fabric containing a polyamide resin. The fine porous film may be made of a polyolefin resin (polyethylene, polypropylene, polybutylene or polyvinyl chloride). Polyolefin resins are preferred because such separators can reduce the total thickness of the separator, which increases the ratio of active materials and conductive materials in the rechargeable battery and ultimately increases the size of the rechargeable battery.

[0065] The electrolyte solution is a solution of a supporting electrolyte dissolved in an organic solvent. The supporting electrolyte is a lithium salt, such as LiPF 6 、LiAsF 6 , LiBF 4 、LiSbF 6 、LiAlCl 4 、LiClO 4 CF 3 SO 3 Li, C 4 F 9 SO 3 Li, CF 3 COOLi, (CF 3 CO) 2 NLi, (CF 3 SO 2 ) 2 NLi and (C 2 F 5 SO 2 )NLi. LiPF6 is preferred because it is easily dissolved in the solvent and exhibits a high degree of dissociation. The organic solvent may be a carbonate ester such as dimethyl carbonate (DMC), ethylene carbonate (EC), fluoroethylene carbonate (FEC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC) and ethyl methyl carbonate (EMC); an ester such as γ-butyrolactone and methyl formate; an ether such as 1,2-dimethoxyethane and tetrahydrofuran; and a sulfur-containing compound such as cyclopentane and dimethyl sulfoxide.

[0066] Examples

[0067] The invention is illustrated by the following non-limiting examples.

[0068] The following materials were used as provided:

[0069] The monomer units acrylonitrile and methacrylic acid come from Sigma-Aldrich, and 1,3-butadiene comes from INEOS.

[0070] SolutionFe(II)SO 4 : Premixed solution contains 0.986 g Fe(II)SO in 400 g water 4 * 7 H2O and 2.0g Rongalit ® C.

[0071] EDTA: used as complexing agent, from Sigma-Aldrich.

[0072] Fatty acid: CAS 67701-08-8, emulsifier for polymerization.

[0073] SDS: Sodium dodecyl sulfate CAS 151-21-3, emulsifier for polymerization.

[0074] t-DDM: Molecular weight regulator from Arlanxeo Deutschland GmbH.

[0075] Trigonox from Akzo-Degussa ® NT50, p-Menthane hydroperoxide. Initiator for emulsion polymerization.

[0076] Diethylhydroxylamine: polymerization terminator, CAS 3710-84-7.

[0077] Dry monochlorobenzene (MCB) from VWR Corporation (VWR).

[0078] Wilkinson catalyst from Materia Inc. and triphenylphosphine from VWR as hydrogenation catalyst

[0079] Gamma-valerolactone (GVL) from Sigma-Aldrich.

[0080] Solef ® 5130 as polyvinylidene fluoride resin with a molecular weight of 1300 kDa

[0081] Kynar ®HSV 900, as a melt viscosity of 48-52,5 kpoise (230 ° C, 100 s -1 ) polyvinylidene fluoride resin

[0082] Lithium iron phosphate: active material; A8-4E, from Hubei Wanrun New Energy Technology Co., LTD.

[0083] Conductive carbon black: Conductive material; Super C65; from Imerys Graphite & Carbon.

[0084] Aluminum foil: current collector; thickness 20 µm; from China AluminiumShanxi New Material Co., Ltd.

[0085] Lithium disc: anode; ø 16 mm, from Tianjin Zhongneng Lithium Co., Ltd.

[0086] Porous polyolefin membrane: as separator, thickness 38 µm (Celgard ® 2340), stamped into ø 18 mm discs; from Celgard.

[0087] Electrolyte solution supporting electrolyte LiPF 6 (Aldrich). Electrolyte solution: 1 M in EC / EMC mixture, EC / EMC = 30 / 70 (v / v) with 2 wt% VC. Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and vinylene carbonate (VC): organic solvents for the electrolytic solution.

[0088] Battery container: Coin cell: Housing; Type 2032, from Shanxi LiZhiYuan Battery Material Co., Ltd.

[0089] Overcurrent prevention device: Sponge nickel: 1 mm thickness per layer, 4 layers per coin cell, from Changsha LiYuan New Material Co.

[0090] 3M tape: Vinyl electrical tape (width 17.5 mm), from 3M China Company.

[0091] Test Method

[0092] Acrylonitrile content:

[0093] The nitrogen content for determining the acrylonitrile content was determined according to the Kjeldahl method (DIN 53 625).

[0094] Solubility:

[0095] The samples were dissolved according to the following procedure and their solubility was evaluated using the standards that followed.

[0096] The samples were placed in the given solvent at the given concentration and shaken at 150 rpm at room temperature using an IKA shaker KS 4000i control model. After the given time, the samples were visually evaluated.

[0097] -- The sample is not dissolved

[0098] - Sample starts to dissolve, particles swell and most of the sample remains undissolved

[0099] 0 Sample begins to dissolve, particles remain undissolved

[0100] + Most of the sample is dissolved, with a small amount of residue or partial turbidity

[0101] ++The sample dissolved completely and showed no residue

[0102] Mooney viscosity:

[0103] The values ​​for the Mooney viscosity (ML 1+4 at 100° C.) were in each case determined at 100° C. in accordance with DIN 53523 / 3 or ASTM D 1646 by means of a shear disk viscometer.

[0104] NMR:

[0105] The 1H NMR spectra were determined by Bruker DPX400 with XWIN-NMR 3.1 software, measuring frequency 400 MHz, solvent CDCl 3 ) to determine the microstructure and termonomer content of individual polymers.

[0106] Method for evaluating discharge specific capacity:

[0107] The produced secondary battery was charged at 0.1 C rate at 23 ° C until the battery voltage reached 4.0 V. Subsequently, after 20 minutes, constant current discharge was performed at 0.1 C rate at 23 ° C until the battery voltage reached 2.8 V. Thereafter, the secondary battery of the coin cell was charged and discharged in constant current mode (CC mode 0.5 C rate). Between each cycle, the battery cell rested for 5 min. The discharge specific capacity of the secondary battery was calculated as the average value between the 2nd and 5th cycles.

[0108] Method for evaluating capacity retention rate:

[0109] The coin cell secondary battery was charged and discharged in constant current mode (CC mode 0.2 C rate) for 50 cycles. The capacity retention was determined as the ratio of the discharge specific capacity after 50 cycles to the discharge specific capacity after the second cycle, expressed as a percentage.

[0110] Preparation of Inventive and Comparative Polymers

[0111] The hydrogenated butadiene-acrylonitrile copolymer and the hydrogenated butadiene-acrylonitrile-methacrylic acid terpolymer were produced according to the basic recipe specified in Table 1, wherein all raw materials are expressed in parts by weight based on 100 parts by weight of the monomer mixture. Table 1 also specifies the corresponding polymerization conditions.

[0112] Table 1: Components for the manufacture of acrylonitrile butadiene rubber copolymers C to I

[0113]

[0114] The polymer was prepared batchwise in a 5 L autoclave with a stirrer system. In each autoclave batch, 1.25 kg of the monomer mixture and 2.1 kg total amount of water and equimolar amounts of EDTA based on Fe(II) were used. Initially, 1.9 kg of this amount of water was charged into the autoclave with the emulsifier and purged with a nitrogen stream. Thereafter, destabilizing monomers and t-DDM (tert-dodecyl mercaptan) as a molecular weight regulator were added and the reactor was closed. After the reactor contents were allowed to warm up, the Fe(II)SO 4 Premix solution and Trigonox ® The polymerization was started with 1% NT50. The progress of the polymerization was monitored by gravimetric determination of the conversion. When the conversion reported in Table 1 was reached, the polymerization was stopped by adding an aqueous solution of diethylhydroxylamine. Unconverted monomers and other volatile components were removed by steam distillation.

[0115] The antioxidant is mixed with the polymer dispersion and adjusted to a solid content of 17.5% by weight. The resulting dispersion containing the additional anti-aging components is then subjected to coagulation, washing, dewatering and drying according to procedures known in the art, either by adding calcium salts or by adding acids to lower the pH.

[0116] The following hydrogenation was carried out in a 10 L high-pressure reactor under the following conditions. For this purpose, the polymer was dissolved in monochlorobenzene (MCB) at a given solids content:

[0117] Solids concentration: 12% - 13% by weight of polymer in MCB

[0118] Reactor temperature: 137°C - 140°C

[0119] Response time: up to 4 hours

[0120] Catalyst: Wilkinson catalyst, triphenylphosphine as co-catalyst

[0121] Hydrogen pressure: 8.4 MPa

[0122] Stirring speed: 600 rpm

[0123] The polymer solution was stirred vigorously with H 2 (23 ° C, 2 MPa) degassing 3 times. The temperature of the reactor was raised to 100 ° C and H 2 The pressure was raised to 6 MPa. A monochlorobenzene solution consisting of Wilkinson's catalyst and a cocatalyst was added and the pressure was raised to 8.4 MPa, while the reactor temperature was adjusted to 137°C-140°C. The temperature and pressure were kept constant during the reaction. The progress of the reaction was monitored by IR spectroscopy by measuring the residual double bond content.

[0124] The reaction was terminated when a residual double bond content of < 5% was reached by releasing the hydrogen pressure.

[0125] The resulting hydrogenated polymer was separated from the solution by steam condensation. For this purpose, the monochlorobenzene solution was diluted to a polymer content of 7% by weight and metered continuously into a stirred glass reactor filled with water and preheated to 100° C. At the same time, 0.5 bar of steam was used to introduce the condensed water. The polymer precipitated as crumbs was dehydrated and then dried under vacuum at 55° C.

[0126] The composition, monomer unit content, residual double bond % and Mooney viscosity of the corresponding hydrogenated polymers are shown in Table 2.

[0127] The spectra of the polymer before, during and after the hydrogenation reaction were recorded on a Perkin Elmer spectrum 100 FT-IR spectrometer. The solution of the polymer in monochlorobenzene was poured onto a KBr plate and dried to form a film for testing. The hydrogenation conversion was determined by FT-IR analysis according to ASTM D 5670-95 method.

[0128] A metathesis reaction is carried out to reduce the molecular weight of the nitrile rubber before hydrogenation of the polymer G. Metathesis is known, for example, from WO-A-02 / 100941 and WO-A-02 / 100905 and can be used to reduce the molecular weight.

[0129] Table 2: Properties of polyvinylidene fluoride resins A (Krynar HSV 900) and B (Solef 5130) and hydrogenated polymers C to I

[0130]

[0131] a) Molecular weight: about 1000 kDa; b) Molecular weight: 1300 kDa; c) nd: Undetermined

[0132] Polymer C is a terpolymer according to the invention, and polymers E and F are copolymers according to the invention (dipolymers). Polymers A and B are PVDC polymers and are therefore comparative. In addition, copolymers D, G and I and terpolymer H have a content of monomer units derived from 1,3-butadiene of more than 65 wt.-% and are therefore also comparative.

[0133] The results from Table 2 show that polymers C to G at least maintain lower density compared to PVDF (polymers A and B).

[0134] The polymer samples were dissolved in γ-valerolactone at room temperature and their solubility was evaluated after 90 min. Polyvinylidene fluoride resins A and B were completely insoluble in γ-valerolactone at room temperature, while hydrogenated polymers C, E, and F were easily soluble in γ-valerolactone at room temperature, leading to an increase in battery cell productivity and energy savings in the preparation process. In addition, the solubility performance was independent of the molecular weight of the hydrogenated nitrile rubber.

[0135] Table 3: Solubility of comparative polyvinylidene fluoride resins A (Krynar HSV 900) and B (Solef 5130) and hydrogenated polymers C to I

[0136]

[0137] The results in Table 3 show that the hydrogenated polymers with the least amount of polar monomers (acrylonitrile and optionally methacrylic acid) have good solubility in γ-valerolactone at room temperature, while polyvinylidene fluoride resin is completely insoluble. Therefore, hydrogenated polymers C, E and F can be used to replace the toxic battery solvent NMP to achieve the use of the non-toxic solvent γ-valerolactone to prepare the binder solution at room temperature.

[0138] General method for coin cell manufacturing

[0139] Step (1) - Dissolution : A certain amount of polymer was dissolved in a solvent (γ-valerolactone) in an oscillator at room temperature overnight to form an adhesive solution (8 wt.-%).

[0140] Step (2) - Preparation of cathode slurry composition : The binder solution from step 1 was mixed with the conductive material (conductive carbon black Super C65) in a new base mixer (milling conditions: 2000 rpm, 12 minutes, room temperature). Thereafter, the active material (LFP, C-coated, A8-4E) and half of the solvent (γ-valerolactone) were added (milling conditions: 2000 rpm, 18 minutes, room temperature), and finally the remaining solvent (γ-valerolactone) was added (milling conditions: 2000 rpm, 6 minutes, room temperature) to obtain the cathode slurry composition.

[0141] Table 4: Battery cell formulation

[0142]

[0143] Weight ratio: for 60% total slurry solids content, LFP / polymer / γ-valerolactone / Super C65 = 96 / 2 / 67 / 2 (polymer concentration in γ-valerolactone = 8 wt.-%)

[0144] Step (3) - Production of cathode disc : The cathode slurry composition was applied to the current collector (aluminum foil) using a bar coater at a coating speed of 4.1 mm / s to form a cathode sheet. The coater slit gap of the coater was adjusted to 250 µm to obtain a predetermined coating thickness.

[0145] Step (4) - Drying: The cathode sheet was dried in an oven at 120°C for 240 minutes to remove solvent and moisture. After drying, the cathode sheet was first compressed with a hot press and then calendered with a double roller device until the dry thickness was reduced by 20% and the surface density was adjusted. A cathode disk (ø 16 mm) was punched out from the calendered cathode sheet using a machine from Shenzhen Poxon MachineryTechnology Co., Ltd., model: PX-CP-S2, model: PX-CP-S2. The punch edge was sharp and burr-free.

[0146] Step (5) - Assembly of lithium-ion secondary battery : Assembly and pressing of lithium-ion secondary batteries were performed in a glove box. The assembly includes the top of the coin cell case (2032 type; negative electrode), supports (stainless steel gasket × 2 and springs), a lithium disk (as anode), a porous separator (Celgard 2400), a cathode disk, and the bottom of the case (positive electrode). All parts were assembled layer by layer. The electrolyte solution (140 µL, 1 M / LLiPF6 in EC / EMC = 30 / 70 (v / v) with 2 wt% VC) was dripped during the assembly step in order to completely fill the free volume of the coin cell. Finally, the coin cell case was pressed by a press in the glove box. An open circuit voltage test was performed to check whether a short circuit occurred.

[0147] Table 5 :Determination of discharge specific capacity and capacity retention rate of lithium-ion batteries (Examples A, CF)

[0148]

[0149] a) np: Since it is not soluble or has poor solubility in γ-valerolactone, it is not possible to prepare an electrode, so it cannot be determined

[0150] The results in Table 5 show that high specific capacity can be obtained by using fluorine-free hydrogenated polymers C, E and F, and good capacity retention can be maintained by using non-toxic solvents for battery processing. Therefore, it is possible to replace the toxic battery solvent NMP and obtain a battery cell with high capacity and capacity retention by using the nitrile rubber of the present invention.

[0151]

[0066] Having thus described the invention and its advantages, it should be understood that the various aspects and embodiments of the invention as disclosed herein are merely illustrative of specific ways to make and use the invention.

[0152] The various aspects and embodiments of the present invention do not limit the scope of the invention when considered in light of the appended claims and the foregoing detailed description.

[0153] What is desired to be protected by Letters Patent is set forth in the following claims.

Claims

1. A composition for manufacturing a cathode of a battery cell, the composition comprising (i) A polymer comprising or consisting essentially of monomeric units derived from: -1,3-butadiene, -Acrylonitrile and - optionally, methacrylic acid, wherein the weight content of monomer units derived from 1,3-butadiene is at most 65 wt.-% relative to the total weight of the polymer; and (ii) γ-Valerolactone.

2. The composition according to claim 1, wherein The polymer is hydrogenated.

3. The composition according to claim 2, wherein The content of residual C═C double bonds is at most 5% relative to the content of C═C double bonds before hydrogenation.

4. A composition according to any one of the preceding claims, wherein The polymer has a weight content of monomer units derived from 1,3-butadiene in the range from 55 to 65 wt.-%, relative to the total weight of the polymer.

5. A composition according to any one of the preceding claims, wherein The polymer has a weight content of monomer units derived from acrylonitrile of at least 25 wt.-%, relative to the total weight of the polymer.

6. A composition according to any one of the preceding claims, wherein The polymer has a weight content of monomer units derived from acrylonitrile in the range from 30 to 45 wt.-%, relative to the total weight of the polymer.

7. A composition according to any one of the preceding claims, wherein Relative to the total weight of the polymer, the polymer has - a weight content of monomer units derived from 1,3-butadiene in the range of 55 to 65 wt.-%; and - a weight content of monomer units derived from acrylonitrile in the range from 35 to 45 wt.-%.

8. A composition according to any one of the preceding claims, wherein The polymer contains no monomer units derived from methacrylic acid.

9. The composition according to any one of claims 1 to 6, wherein The polymer has a weight content of monomer units derived from methacrylic acid of at least 2.5 wt.-%, relative to the total weight of the polymer.

10. The composition according to claim 9, wherein The polymer has a weight content of monomer units derived from methacrylic acid in the range from 2.5 to 7.5 wt.-%, relative to the total weight of the polymer.

11. The composition according to claim 9 or 10, wherein Relative to the total weight of the polymer, the polymer has - a weight content of monomer units derived from 1,3-butadiene in the range of 55 to 65 wt.-%; - a weight content of monomer units derived from acrylonitrile in the range of 30 to 45 wt.-%; and - a weight content of monomer units derived from methacrylic acid in the range from 2.5 to 7.5 wt.-%.

12. A composition according to any one of the preceding claims, the polymer consisting essentially of monomer units derived from the following monomers in the following amounts relative to the total weight of the polymer: (i) 1,3-butadiene 62 ± 2 wt.-%, acrylonitrile 33 ± 2 wt.-% and methacrylic acid 5 ± 2 wt.-%; (ii) 1,3-butadiene 61 ± 2 wt.-% and acrylonitrile 39 ± 2 wt.-%; or (iii) 1,3-Butadiene 57 ± 2 wt.-% and acrylonitrile 43 ± 2 wt.-%.

13. Use of a composition according to any one of the preceding claims for producing a cathode for a battery cell.

14. A cathode for a battery cell obtained from the composition according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Binder composition for nonaqueous secondary battery positive electrodes, composition for nonaqueous secondary battery positive electrodes, positive electrode for nonaqueous secondary batteries, and nonaqueous secondary battery

    EP3605675A1

  • All-solid type secondary battery, electrode sheet for all-solid type secondary battery, and manufacturing methods thereof

    JP2017045611A

  • Porous membrane forming composition, separator, electrochemical element, and method for producing electrode complex

    JP2018076417A

  • Additive, electrolyte for lithium secondary battery and lithium secondary battery including the same

    US20200194837A1

  • Binder composition for electrode for lithium-ion secondary battery and utilization thereof

    WO2000045452A1